2019
DOI: 10.1371/journal.pone.0211172
|View full text |Cite
|
Sign up to set email alerts
|

Selection and validation of reference genes for quantitative Real-Time PCR in Arabis alpina

Abstract: Arabis alpina is a perennial arctic-alpine plant and an upcoming model organism for genetics and molecular biology for the Brassicaceae family. One essential method for most molecular approaches is the analysis of gene expression by reverse-transcription quantitative Real-Time PCR (RT-qPCR). For the normalisation of expression data in RT-qPCR experiments, it is essential to use reliable reference genes that are not affected under a wide range of conditions. In this study we establish a set of 15 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Liu et al 27 analyzed perennial ryegrass under high-temperature stress and identified HIS3 and eIF4A as the most suitable reference genes. In another study, EF-1α and UBQ were detected as the most stable internal reference genes in potato and Arabis alpina under drought conditions 28 , 29 . Therefore, verifying the expression stability of reference genes under different experimental conditions is critical when selecting reference genes to standardize gene expression levels.…”
Section: Discussionmentioning
confidence: 95%
“…Liu et al 27 analyzed perennial ryegrass under high-temperature stress and identified HIS3 and eIF4A as the most suitable reference genes. In another study, EF-1α and UBQ were detected as the most stable internal reference genes in potato and Arabis alpina under drought conditions 28 , 29 . Therefore, verifying the expression stability of reference genes under different experimental conditions is critical when selecting reference genes to standardize gene expression levels.…”
Section: Discussionmentioning
confidence: 95%
“…(C) The expression levels of AaSPI were determined in the above ground parts of seedlings of pep1 , Aaspi-1 , Aaspi-2 , and Aaspi-3 by qPCR. Normalization was carried out using AaTUA5 and AaCAC ( Stephan et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Higher dilutions were not possible due to the concentration of RNA/cDNA. Primers for reference genes were described before ( Wang et al, 2009 ; Stephan et al, 2019 ). Primers for genes of interest were accepted with an efficiency of 80–120% and a correlation between −1 and −0.99 ( Supplementary Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, gene expression analyses are affected by many factors such as the quality of RNA samples, the efficiency of reverse transcription, and PCR efficiency 2 , 3 . For accurate comparisons of expression levels, the expression data of the genes of interest are normalized against the expression data for a reference gene 4 . Moreover, the reference gene compensates for the above-mentioned limitations 5 .…”
Section: Introductionmentioning
confidence: 99%